VALUE OF UTILIZING AGRICULTURAL WASTE FOR FISH FEED (CASE STUDY OF FISH PELLET FEED) - Eko Sumartono; Mujiono Mujiono; Johnny Oktapriza; Fetri Yuliana (Universitas Mataram, 2024)
Most of the residents in Central Bengkulu Regency work as farmers, in addition to raising livestock and as fish cultivators. This condition needs serious attention from the local government and related stakeholders. The issue of feed has a large proportion of the sustainability of livestock businesses. On the other hand, palm fronds as post-harvest agricultural waste and bran as post-processing waste have not been utilized optimally. Even though the nutritional content contained in it is quite high. Agricultural and plantation waste by-products have good potential for use as animal feed. In order to guarantee safety and suitability, further processing and analysis is needed. Processing of raw materials is carried out in a combination (physical, chemical and biological). Preparation of feed formulations using Pearson's Quadrilateral Method. Testing is carried out in laboratories that consistently apply ISO/IEC 17025: 2017 from the National Accreditation Committee (KAN), namely the Animal Husbandry Service Service of East Java Province. The test result standard refers to SNI 01-4087-2006 concerning Artificial Feed for Catfish (Enlargement). Fish feed (pellets) that meet SNI 01-4087-2006 contain 3 types of content including ash content, crude fat, and aflatoxin. Types of content that do not meet SNI are crude protein, crude fiber, phosphorus, buoyancy and pellet diameter. The estimated cost of making fish food (pellets) costs around IDR. 6,100,- per kilogram. Cost analysis is relevant to feed quality and daily requirements without reducing nutritional value. Further research is needed to ensure that artificial feed is more cost efficient than conventional feed.